(untitled) (Research, Society and Development, 2025)
As an alternative to the use synthetic fungicides in the control of agricultural pests, research is being directed to natural compounds, called biopesticides. Microalgae produce a wide variety of bioactive molecules, with several biological activities already recorded, including antifungal against phytopathogens. According to that, the objective of this study was to evaluate in vitro antifungal activity of the microalgae Conticribra weissflogii and Tetraselmis suecica against the phytopathogen Colletotrichum gloeosporioides. To obtain the microalgal biomass, cultures were carried out in 10 L reactors, in triplicates. The biomass was subsequently freeze-dried and then went through the extraction process using as solvent absolute ethanol (99,99%). The antifungal activity of the extracts was evaluated by the broth microdilution methodology, with a concentration range of 0.115 to 6 mg mL⁻¹. The Minimum Inhibitory Concentration (MIC) was determined visually, by the absence of fungal growth. The microalgae C. weissflogii showed fungistatic activity, with a MIC of 1.5 mg mL⁻¹ and T. suecica did not register inhibition of the fungus evaluated. This study highlights the potencial of eukaryotic microalgae as sources of alternative antifungal compounds to synthetic pesticides, a more environmentally sustainable option. In addition, this is a pioneering work on the antifungal activity of these microalgae species against the phytopathogen C. gloeosporioides. Further research may be carried out aiming the isolation and identification of active biomolecules of C. weissflogii with antifungal property, as well as, in the future, new biopesticides may be formulated from this extract.